The Identity of Ba Alawi women islamic communicators: Najwa Shihab and Halimah Alaydrus as models - Sadili, Imam; Zaidan, Ashraf Muhammed (Faculty of Dakwah and Communication, Walisongo State Islamic University, 2024)
Purpose - This research aims to uncover the identity of Ba Alawite women Islamic communicators, regarding their background of being closed (exclusive) while others are a small part of being inclusive. Also, to explain their transformation from exclusive to inclusive. This research is important to know the gender equality of Ba Alawy women.Method - This research is qualitative with the type of literature review. Data is obtained from YouTube channels, journals, books, and related websites. The theory used is Mary Jane Collier's cultural identity theory.Result - Ba Alawi women are closed because of communication with Tarim customs and traditions carried out since childhood, in this case, Halimah Alaydrus. At the same time, Najwa Shihab is an inclusive Ba Alawi woman whose identity has been influenced by openness since childhood in communicating with all traditions and thoughts.Implication – This article is intended to provide encouragement and knowledge about the diversity of Ba Alawi women; the majority of them are exclusive, and a small number are inclusive. The climate in Indonesia and Hadramut is not the same. And Ba Alawi women need to take opportunities in the world of da'wah.Originality/Value - This research is the first on female Islamic communication actors from among the ba alawy and their role in the world of da'wah, as well as their inclusive or inclusive life motives.***Tujuan - Penelitian ini bertujuan untuk mengungkap identitas komunikator Islam perempuan Ba Alawite, mengenai latar belakang mereka yang tertutup (eksklusif) dan sebagian kecil yang inklusif. Selain itu, untuk menjelaskan transformasi mereka dari eksklusif menjadi inklusif. Penelitian ini penting untuk mengetahui kesetaraan gender perempuan Ba Alawy.Metode - Penelitian ini bersifat kualitatif dengan jenis tinjauan literatur. Data diperoleh dari kanal YouTube, jurnal, buku, dan situs web terkait. Teori yang digunakan adalah teori identitas budaya Mary Jane Collier.Hasil - Perempuan Ba Alawi tertutup karena komunikasi dengan adat dan tradisi Tarim yang dilakukan sejak kecil, dalam hal ini Halimah Alaydrus. Sementara itu, Najwa Shihab merupakan perempuan Ba Alawi yang inklusif yang identitasnya dipengaruhi oleh keterbukaan sejak kecil dalam berkomunikasi dengan semua tradisi dan pemikiran.Implikasi - Artikel ini dimaksudkan untuk memberikan dorongan dan pengetahuan tentang keberagaman perempuan Ba Alawi yang mayoritas bersifat eksklusif dan sebagian kecil bersifat inklusif. Iklim di Indonesia dan Hadramut tidak sama. Dan perempuan Ba Alawi perlu mengambil peluang dalam dunia dakwah.Orisinalitas/Nilai - Penelitian ini merupakan penelitian pertama tentang pelaku komunikasi Islam perempuan dari kalangan ba alawy dan peran mereka dalam dunia dakwah, serta motif hidup mereka yang inklusif atau tidak.